Large Eddy Simulation of Turbulent Flow and Heat Transfer in a Ribbed Coolant Passage - Abhishek G. Ramgadia; Arun K. Saha (Journal of Applied Mathematics)
Numerical simulations of hydrodynamic and thermally fully developed turbulent flow are presented for flow through a stationary duct with periodic array of inline transverse rib turbulators. The rib height to hydraulic diameter ratio (𝑒/𝐷ℎ) is 0.1 and the rib pitch to rib height ratio (𝑃/𝑒) is 10. The effect of secondary flow due to presence of rib turbulators on heat and mass transfer has been investigated. The present work reviews the use of a large eddy simulation (LES) turbulence model, known as shear-improved Smagorinsky model (SISM), for predicting flow and heat transfer characteristics in the fully developed periodic flow region. The computations are performed for Reynolds number of 2,053 and the working fluid chosen to be air, the Prandtl number of which is 0.7. Instantaneous flow field, time-mean, and turbulent quantities are reported together with heat transfer and a close match with experiments has been observed.